The Influencing factors of Female Passenger Background in Online Transportation with Perceived Ease of Use - Meyliana Meyliana; Surjandy Surjandy; Erick Fernando; Firman Anindra (ComTech: Computer, Mathematics and Engineering Applications, 2019)
This research aimed to explore the correlation or influence factors between the background of female passengers with perceived ease of use factors in Online Transportation Application (OTA). This research was explanatory and descriptive (causal) research. The respondents were the female users of OTA. The total of respondents was 408 people. SPSS applications were used to process the data. Then, the cross-tabulation was to find the correlation or influence factors. In the end, the researchers find 19 factors that are essential for future research.